ANALISA BARU DALAM MENDETEKSI LETAK GANGGUAN HUBUNG SINGKAT JARINGAN 1 FASA - Solly Aryza; Zulkarnain Lubis; Muhammad Isa Indrawan (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
This circuit is only for detecting the location of the 1-phase network short circuit fault. The single power supply that issues the 12 V voltage will be converted into 2 voltage sources, namely voltage (+) and voltage (-). This voltage is used to supply a parallel resistance circuit which functions to find the voltage difference to be measured. The voltage difference is sent to the op-amp. The op-amp used IC TL084 CN which has 4 op-amps and only uses 1 op-amp. After the output voltage from the op-amp, it is sent to the interface (ADC). The signal issued by the op-amp is still analog. Whereas we use a PC that can only receive digital signals. So that we need an interface circuit (ADC) so that the PC can receive signals from the circuit. The cable used to send the signal is using a RS 232 cable or serial USB cable. After the PC receives the signal via a serial USB cable, the signal is processed in Visual Basic 6.0. Before testing the tool, a calibration is carried out so that the resulting data is more accurate and will be displayed in Visual Basic 6.0.